BAHASA JERMAN SEBAGAI JEMBATAN BERKARIR DI JERMAN - Jolanda Tomasouw; Henderika Serpara; Maria M Nikijuluw (German für Gesellschaft (J-Gefüge), 2022)
The best chance for someone to advance their career abroad these days is to be fluent in German. The goals of the virtual community service at SMAN 1 Maluku Tenggara are to (a) enlighten students about employment options in Germany and (b) increase their motivation to learn German through a variety of media. A total of 37 people participated in this activity, including 3 study program lecturers, 30 students majoring in science, social studies, and languages, 3 outstanding German students who were ready to go and work in Germany, and 1 teacher for German courses at the school. German is spoken. The method used in this activity is interactive lectures, wherein each member of the German Language Education Study Program team presents the subject in turn by creating interactive and educative situations in the form of discussions and questions and answers. As well as providing understanding and awareness to students, about how important it is to learn German as a career bridge in Germany, and how to increase motivation to learn German through various media. The evaluation and reflection results revealed that the Community Service activities were enthusiastically welcomed by the students. The data analysis reveals that: (1) Students' perceptions of career opportunities in Germany explain that 54.75% of students are very interested in continuing their studies in Germany; 52.93% of students are very interested in joining the program from the German government for vocational schools; 64% of students are very interested in working in Germany; 54.33% of students are very interested in studying while working at FSJ, and 57.16% are very interested in participating in AuPair program in Germany. This necessitates that German language teachers give these students additional attention and guidance so that they can enhance their understanding of the German language in the study program for German language education or through the available German language courses; (2) Students' satisfaction with their increased motivation to learn German through various media revealed that approximately 59.29% of students were very interested in learning from German books, 56.16% in watching videos and films in German, 62.14% in listening to German songs, 67.95% in watching YouTube in German, and 34.29% in reading Facebook posts on social media in German. In this regard, German language teachers need to provide assistance, so that the information obtained from various media can be explained properly to avoid the wrong concept